+0  
 
+7
112
3
avatar+315 

3x4y3 – 48y3 It would be = 3y3(x4 – 16). right?

 Dec 31, 2020
 #1
avatar+112823 
+3

3x4y3 – 48y3 It would be = 3y3(x4 – 16). right?

 

Maybe you mean   3x^4y^3 – 48y^3 It would be = 3y^3(x^4 – 16). right?

which is

\(3x^4y^3 – 48y^3 = 3y^3(x^4 – 16) ??\)

 

 

Yes that is correct.

 Jan 1, 2021
 #2
avatar+315 
+2

Thank you :p

wolfiechan  Jan 1, 2021
 #3
avatar+315 
+3

Thanks for explaining this in a different way That helped alot UwU

wolfiechan  Jan 2, 2021

9 Online Users